Mechanistic analysis of the cathodic stripping square-wave voltammetric response of the copper‑arsenic system at a mercury electrode - Gómez Avila, Jenny (2020)
Despite arsenite can be reduced to As(0) and deposited at the surface of solid electrodes such as gold, platinum, or copper, it cannot form amalgams with mercury, and so the addition of other metal ions is required for its deposition. In this manuscript, mechanistic analysis of the cathodic stripping square-wave voltammetric response of the system copper‑arsenic is presented. For the analysis of experimental responses, a mathematical model is used to consider that a surface-active reagent undergoes a charge transfer step followed by a chemical reaction. The dependences of the differential peak current, and the respective peak potential and half-peak width on the square-wave frequency were used to estimate the apparent stability constant of arsenide formation and that the electrode reaction would involve the direct transfer of 2 electrons, while the simulation and fit of forward and backward voltammetric responses have been useful for inferring other parameters such as the formal charge transfer rate constant of the global electron transfer reaction, a pseudo-first order homogeneous rate constant associated with arsenide formation, and the charge transfer coefficient of the global electron transfer reaction. Besides the values estimated for each of those parameters, all simulations indicate that the reduction of copper instead of arsenic would be taking place during the cathodic stripping scan. Accordingly, the trace-analysis reaction of arsenic in the presence of copper would be based on the surface accumulation of a metal complex, where Cu2+ would be the metal cation and an arsenide species the ligand. The stability of that complex at the surface of a mercury electrode would depend not only on the applied potential, but also on the ratio between copper, arsenic, and protons.